2011
DOI: 10.1002/j.1532-2149.2011.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture reduces the expression of proinflammatory cytokines in inflamed skin tissues through activation of cannabinoid CB2 receptors

Abstract: Endogenous cannabinoids and peripheral cannabinoid CB2 receptors (CB2Rs) are involved in the antinociceptive effect of electroacupuncture (EA) on inflammatory pain. However, it is not clear how CB2R activation contributes to the antinociceptive effect of EA. The major proinflammatory cytokines, such as tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and IL-6, are involved in inflammatory pain. Here we determined the effects of CB2R activation and EA on the expression level of IL-1β, IL-6 and TNF-α in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 58 publications
2
48
1
1
Order By: Relevance
“…It has been reported that EA increased mechanical threshold in the CFAinduced inflammatory pain model [33]. EA may modulate IL-17RA in DRG neurons to inhibit pain, which warrants further investigation.…”
Section: Fig (5)mentioning
confidence: 89%
“…It has been reported that EA increased mechanical threshold in the CFAinduced inflammatory pain model [33]. EA may modulate IL-17RA in DRG neurons to inhibit pain, which warrants further investigation.…”
Section: Fig (5)mentioning
confidence: 89%
“…Previous research also emphasized the important role of local adenosine A1 receptors in the anti-nociception of acupuncture [7]. Previous studies, including some studies from our laboratory, showed that interleukins, such as IL-1β, are modulated in EA analgesia in inflammatory pain [8,37]. Consistently, we showed here that IL-33, a novel IL-1 family member with a structure similar to that of IL-1β, also played an important role in EA analgesia in acute inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, addressing AT's mechanism of action in WAD patients might pose considerable challenges. Apart from nonspecific psychological (placebo) effects related to the patient's belief that treatment will be effective, the antinociceptive effect of needling might involve a reduction of inflammatory pain and proinflammatory cytokines through the activation of endogenous cannabinoids and peripheral cannabinoid receptors [37, 38]. …”
Section: Discussionmentioning
confidence: 99%